Fruit, vegetable and vitamin C intakes and plasma vitamin C: cross‐sectional associations with insulin resistance and glycaemia in 9–10 year‐old children. Issue 3 (23rd November 2015) - Donin, A. S.; Dent, J. E.; Nightingale, C. M.; Sattar, N.; Owen, C. G.; Rudnicka, A. R.; Perkin, M. R.; Stephen, A. M.; Jebb, S. A.; Cook, D. G.; Whincup, P. H.
Abstract: Aim: To examine whether low circulating vitamin C concentrations and low fruit and vegetable intakes were associated with insulin resistance and other Type 2 diabetes risk markers in childhood. Methods: We conducted a cross‐sectional, school‐based study in 2025 UK children aged 9–10 years, predominantly of white European, South‐Asian and black African origin. A 24‐h dietary recall was used to assess fruit, vegetable and vitamin C intakes. Height, weight and fat mass were measured and a fasting blood sample collected to measure plasma vitamin C concentrations and Type 2 diabetes risk markers. Results: In analyses adjusting for confounding variables (including socio‐economic status), a one interquartile range higher plasma vitamin C concentration (30.9 μmol/l) was associated with a 9.6% (95% CI 6.5, 12.6%) lower homeostatic model assessment of insulin resistance value, 0.8% (95% CI 0.4, 1.2%) lower fasting glucose, 4.5% (95% CI 3.2, 5.9%) lower urate and 2.2% (95% CI 0.9, 3.4%) higher HDL cholesterol. HbA1c concentration was 0.6% (95% CI 0.2, 1.0%) higher. Dietary fruit, vegetable and total vitamin C intakes were not associated with any Type 2 diabetes risk markers. Lower plasma vitamin C concentrations in South‐Asian and black African‐Caribbean children could partly explain their higher insulin resistance. Conclusions: Lower plasma vitamin C concentrations are associated with insulin resistance and could partly explain ethnic differences in insulin resistance. Experimental studies are needed to establish whether increasing plasma vitamin C can help prevent Type 2 diabetes at an early stage. What's new?: We examined the cross‐sectional associations between intakes of fruit, vegetables and vitamin C, circulating vitamin C concentrations and insulin resistance in UK children. Circulating vitamin C concentration was inversely associated with insulin resistance, while intakes of fruit, vegetable and vitamin C were unrelated to insulin resistance. Low levels of circulating vitamin C concentrations in UK South‐Asian children could contribute to their higher insulin resistance. Further studies (including trials) are needed to examine the association of vitamin C with insulin resistance and its potential implications for Type 2 diabetes prevention.